PENDAMPINGAN KOMUNITAS BELAJAR SEKOLAH PENGGERAK MELALUI LOKAKARYA REFLEKSI UNTUK MENINGKATKAN KUALITAS PROSES PEMBELAJARAN DI SEKOLAH DASAR - Asriadi, Asriadi; Nur, Muhammad Awal; Sukaria, Muhammad Ikhsan; Shabir, Achmad (MAJU : Indonesian Journal of Community Empowerment, 2024)
Driving schools, especially elementary schools in Wajo Regency, have several learning communities with different teacher competencies. Most teachers have not fully mastered the differentiation learning process in the Merdeka Belajar curriculum. The aim of this mentoring activity is to assist learning community teachers in planning, organizing and implementing an effective and creative Merdeka curriculum learning process. The method used in this service is a workshop form which includes stages starting from self, collaboration space, contextual demonstration and real action. Meanwhile, the material in this service activity uses teaching materials that have been determined by the Directorate General of Teachers and Education Personnel, Ministry of Education and Culture, Research and Technology. The results of the service show that the learning community that was accompanied has been able to create a plan for real action for a quality learning process that will be implemented in their respective educational units. Apart from that, the participants increasingly understand the function and role of the Learning Community in improving student performance and solving every problem in the Education Unit